Assessment of Traffic-Related Ambient Air Particulate Matter (PM) Levels in Douala, Cameroon - Yannick Cédric Ngangmo; Cyrille Adiang Mezoue; Cyrille Meukaleuni; Brice B. S. Wandjie; David Monkam (Advances in Meteorology)
A challenge in many Sub-Saharan African (SSA) cities is the absence of air quality monitoring due to the high expense and technical expertise needed. Air pollution around the world is becoming a societal problem, and developed countries have all the necessary information about the levels of most air pollutants; however, underdeveloped countries have inadequate information on air quality. The problem of poor air quality in many SSA countries is due to lack of information about the hazards of poor air quality, lack of monitoring equipment, and lack of measuring stations: this is the case in Cameroon. We are avoiding these problems by using portable, low-cost, low-maintenance air quality monitoring equipment, including the OC 300 dust particle laser, to observe pollution levels of particle matter levels in the PK17 Douala-Cameroon, a locality in the Central African region where no air quality data previously existed. The air quality index is very poor on the measurement days, and the color code is red. It has maximum values of about 199 for PM10 and 192 for PM2.5. The average concentration values obtained were of the order of 200.54 µg·m−3, 155.54 µg·m−3, 194.90 µg·m−3, and 194.03 µg·m−3 for PM10, respectively, on Tuesday, Thursday, Saturday, and Sunday. Regarding PM2.5, the average concentrations are 99.84 µg·m−3, 82.30 µg·m−3, 108.23 µg·m−3, and 112.97 µg·m−3, respectively, on Tuesday, Thursday, Saturday, and Sunday. A two-dimensional Gaussian model was used to estimate the particle matter concentration along each road. The nRMSE was 9% for PM10 and 12 for PM2.5, and the index-d for both particle sizes was close to 1 (0.74 for PM10 and 0.98 for PM2.5), which allows us to conclude that the calculated concentrations are the closest to the measured concentrations. The assessment reveals that most of the particulate matter during the measurement period was generated by road traffic. The concentration measured values of the pollutants are three times for PM2.5 and four times for PM10 above the recent WHO limits for daily exposure. In addition, it provides essential information on the pollution in Douala, which can be a major source of illness in the city and must be addressed.